Assessment of Self-Management Treatment Needs Among COPD Helpline Callers. (2nd January 2019) - Mathew, Amanda R.; Guzman, Miriam; Bridges, Cherylee; Yount, Susan; Kalhan, Ravi; Hitsman, Brian
Abstract: Telephone quitlines are an effective population-based strategy for smoking cessation, particularly among individuals with tobacco-related diseases such as chronic obstructive pulmonary disease (COPD). Expanding quitline services to provide COPD-focused self-management interventions is potentially beneficial; however, data are needed to identify specific treatment needs in this population. We conducted a telephone-based survey ( N = 5, 772) to examine educational needs, behavioral health characteristics, and disease-related interference among individuals with COPD who received services from the American Lung Association (ALA) Lung Helpline. Most participants (73.7%) were interested in COPD-focused information, and few had received prior instruction in breathing exercises (33.9%), energy conservation (26.5%), or airway clearing (32.1%). About one-third of participants engaged in regular exercise, 16.3% followed a special diet, and 81.4% were current smokers. Most participants (78.2%) reported COPD-related interference in daily activities and 30.8% had been hospitalized within the past six months for their breathing. Nearly half of participants (45.4%) reported current symptoms of anxiety or depression. Those with vs. without anxiety/depression had higher rates of COPD-related interference (83.9% vs. 73.5%, p < .001) and past six-month hospitalization (33.4% vs. 28.3%, p < .001). In conclusion, this survey identified strong interest in disease-focused education; a lack of prior instruction in specific self-management strategies for COPD; and behavioral health needs in the areas of exercise, diet, and smoking cessation. Anxiety and depression symptoms were common and associated with greater disease burden, underscoring the importance of addressing coping with negative emotions. Implications for self-management treatments that target multiple behavioral needs of COPD patients are discussed.